138k views
4 votes
Simplify (5ab^2c)(-7ab^4c)

2 Answers

3 votes

Answer:


-35a^2b^6c^2

Explanation:

Multiply 5 and -7 = -35

a^1 times a^1 = a^2 (add exponents)

b^2 times b^4 = b^6 (add exponents)

c times c =c^2 (add exponents)

User Janiis
by
5.5k points
5 votes

Answer:

-35a^2b^6c^2

Explanation:

Multiply the numbers like normal and add the variables (a,b,c) exponents.

User Zabumba
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.